1985
DOI: 10.1152/jappl.1985.59.5.1647
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic knee extension as model for study of isolated exercising muscle in humans

Abstract: In an attempt to approach a system of isolated exercising muscle in humans, a model has been developed that enables the study of muscle activity and metabolism over the quadriceps femoris (QF) muscles while the rest of the body remains relaxed. The simplest version includes the subject sitting on a table with a rod connecting the ankle and the pedal arm of a bicycle ergometer placed behind the subject. Exercise is performed by knee extension from a knee angle of 90 to approximately 170 degrees while flywheel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
360
1
14

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(388 citation statements)
references
References 0 publications
13
360
1
14
Order By: Relevance
“…The intersection has been reported to be largely consistent with AT and LT determined by expired gas analysis [4][5][6] . As reported previously, the rate of increase in SBP is low with low workload and becomes higher with a workload above a certain intensity, and an excess increase in blood pressure is associated with greater activation of baroreceptors and suppression of sympathetic nerve activity 7) . This indicates that blood pressure increase is inhibited with greater intensity of exercise.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The intersection has been reported to be largely consistent with AT and LT determined by expired gas analysis [4][5][6] . As reported previously, the rate of increase in SBP is low with low workload and becomes higher with a workload above a certain intensity, and an excess increase in blood pressure is associated with greater activation of baroreceptors and suppression of sympathetic nerve activity 7) . This indicates that blood pressure increase is inhibited with greater intensity of exercise.…”
Section: Introductionsupporting
confidence: 75%
“…In addition, when subjects had a habit of exercising daily, HR was 75.4% for men and 66.7% for women at DPBP. In general, AT and HR at DPBP are said to be higher for people who exercise daily than for people 7) reported that the blood pressure response is constant at small load and that it begins to increase beyond a threshold load limit. In other words, one could suggest that HR and SBP are controlled by a pressure receptor-a chemical receptor of aortic arch and sinus caroticus-during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Koga et al (25) directly compared KE and leg cycling exercise and reported a higher V O 2 G during KE (ϳ12 ml⅐min Ϫ1 ⅐W Ϫ1 ) compared with leg cycling exercise (ϳ9 ml⅐min Ϫ1 ⅐W Ϫ1 ), regardless of whether the exercise was performed at the same absolute (i.e., 66 W) or relative intensity (KE, 38 W; leg cycling, 66 W). It is not clear why the V O 2 G is greater in KE than leg cycling exercise; however, muscle work during KE exercise is restricted mainly to the quadriceps muscle group, whereas a number of muscles groups, including muscles of the upper and lower leg, are recruited during leg cycling exercise (1,21,30), and thus differences may relate to the combined metabolic and/or mechanical efficiencies of the muscles used during the different exercise modes.…”
Section: Discussionmentioning
confidence: 99%
“…The arterial catheter was 20 G and 20 cm (Ohmeda, Swindon, UK), and the venous catheter was a radiopack TFE catheter with side holes (Cook, Bjaevershou, Denmark). A thermistor was inserted through the venous catheter for blood flow measurements by the constant infusion thermodilution technique (1). Thirty minutes after placement of the catheters, breath and blood samples were obtained for assessment of background enrichment of breath and blood CO 2 and blood lactate and glucose.…”
Section: Methodsmentioning
confidence: 99%